Rationale and design of a pilot study to evaluate the acceptability and effectiveness of a revised protein sparing modified fast (rPSMF) for severe obesity in a pediatric tertiary care weight management clinic - Eneli, I.U. (Contemp Clin Trials Commun, 2019)
Aggressive dietary interventions may provide an accessible treatment option for children and adolescents with severe obesity who are not successful with traditional lifestyle behavioral interventions or do not want or qualify for weight loss surgery. One such intensive dietary option is the protein sparing modified fast (PSMF). The PSMF involves minimal carbohydrate intake to induce ketosis, while maintaining adequate or high protein intake to minimize catabolism. The PSMF, under medical supervision, can be an effective and safe intervention for children and adolescents, yet the PSMF diet is not regularly used in the treatment of pediatric severe obesity. This paper describes the rationale and design for a pilot study to evaluate the acceptability and effectiveness of a revised PSMF (rPSMF) implemented as a weight loss treatment option for children and adolescents with severe obesity in a pediatric tertiary care weight management clinic. The primary aim of the study is to evaluate the acceptability of the rPSMF as assessed by adherence, satisfaction with the intervention, and participation rate using quantitative and qualitative methods. The secondary aim is to investigate the effectiveness of the rPSMF on improving a) anthropometric measures (weight, body mass index [BMI], BMI z-score); b) metabolic measures (lipid profile, glycosylated hemoglobin, liver function tests); and c) quality of life. Results of this study will provide guidance for the standardization of a pediatric rPSMF protocol in a clinic setting, delineate which factors improve or hinder adherence and weight loss and provide preliminary data for a multicenter randomized controlled trial. CLINICALTRIALS.GOV IDENTIFIER: NCT03899311.